Understanding Terrorist Radicalization and Extremism: Building Sustainable Recovery Strategies from Terrorism (قضايا سياسية, 2024)
Combating terrorism and extremism requires significant efforts from all segments of society, including governments, local communities, and international entities, to ensure sustainable recovery, and in return there is no coordination between the international community to establish a system to confront it effectively and permanently. Steady approaches are being taken, and its devastating effects on lives, facilities and others are no longer hidden, until it comes to the point of threatening the economic, social and political conditions of countries. Among the challenges, developments and rapid and comprehensive events in all aspects of life, like many countries of the world, and among these challenges that have emerged in the past two decades is the phenomenon of terrorism, extremism and intellectual deviation, which is basically a departure from the approach of moderation, moderation and tolerance, and since terrorism has turned into a phenomenon Efforts should be devoted to researching the causes of this dangerous scourge and developing solutions and policies to combat it, confront it by various means, and achieve sustainable recovery from it. This is done by presenting the subject through the following axes. Conceptual rooting of the terms (terrorism, violent extremism and terrorist radicalism) the most important strategies for recovery from terrorism.